Integrated plasma and tissue proteomics reveals attractin release by intraluminal thrombus of abdominal aortic aneurysms and improves aneurysm growth prediction in humans - Lee, R; Cassimee, I; Huang, H; Lapolla, P; Ngetich, E; Chandrashekar, A; Charles, P; Kessler, B; Fischer, R; Handa, A (Lippincott, Williams & Wilkins, 2020)
Objective: Discovery of novel biomarkers for abdominal aortic aneurysm growth (AAA) prediction.